Web-based rehabilitation aftercare following inpatient psychosomatic treatment Web-basierte Rehabilitationsnachsorge nach stationärer psychosomatischer Therapie (W-RENA) - Ebert, David Daniel; Hannig, Wiebke; Tarnowski, Torsten; Sieland, Bernhard; Götzky, Benjamin; Berking, Matthias (Rehabilitation, 2013)
Background: High relapse rates following treatment for mental health disorders are a challenge for psychosomatic rehabilitation treatments. The goal of the present study is to evaluate the feasibility, acceptance and process-quality of a 12-week transdiagnostic Internet-based maintenance treatment (W-RENA) following psychosomatic rehabilitation treatment. Findings regarding effectiveness and moderators of treatment outcome that were already reported elsewhere are briefly summarized. Method: In a preliminary study we first assessed whether rehab patients have the technical requirements and abilities to successfully participate in Internet-based treatments. Patients expressing interest for participation in W-RENA (N=400) were compared with non-participants (N=1 789) with regard to sociodemographic and clinical characteristics. In a 2-arm randomized controlled trial (N=400) we subsequently compared participants of W-RENA with participants of a treatment as usual group (TAU). Self-report measures were assessed at the beginning of inpatient treatment (t1), at discharge from inpatient treatment/start of W-RENA (t2), and at 3- (t3) and 12-months follow-ups (t4). Results: The majority of assessed rehab-patients had the technical prerequisites (78.79%) and necessary skills (79.9%) to successfully participate in an Internet-based intervention. A third of the patients (32%) which were invited to take part in the intervention (and the study) expressed interest to participate. Study participants and non-participants differed only slightly. Most participants (80.6%) reported to have gained benefit from participating. Treatment achievements as well as quality of therapist alliance were rated high from both patients and therapists. Moreover, participants of the W-RENA group could stabilize their inpatient treatment outcomes up to 3- and 12-months follow-up better than controls could do (differences in symptom change from discharge to 3-months follow-up: d=0.38; to 12-months follow-up: d=0.55). Clinical significant symptom deterioration from discharge to 1-year follow-up could be reduced by 2/3 (29.45% vs. 11.45%). We could not identify any subgroup not profiting from study participation. Patients with low education benefited particularly. Conclusion: Internet-based aftercare interventions are a feasible, accepted and effective approach to successfully sustain treatment outcomes achieved in inpatient psychosomatic rehabilitation. © Georg Thieme Verlag KG Stuttgart. New York.
Created from Fastlane, Scopus look-up
Keywords: aftercare; internet therapy; internet-based guided self-help; relapse prevention; social network